An Explanation of the Sufi Terms Used in Khawaja Yusuf Hamadânî’s Works - Mansurov, Fatkhiddin (Universiti Putra Malaysia, 2017)
It is well known that a considerable amount of important work has been written in the area of Sufism up to the present day. Sufism aims to nourish the inner dimension of a human being. Therefore, the most crucial purpose of Sufism is to provide the flourish of faith in the hearts of many in terms of the key principles of the Qur’an and the Sunna. Sufism has its own terminology which is necessary to be clearly understood in order appreciate the real meaning of the Sufi doctrines. One of the significant Sufi scholars in the history of Sufism, Khawaja Yusuf Hamadânî (d. 535H/1140M), had completed a number works written in both Persian and Arabic. These works had been written concisely and consisted of the key principles of a spiritual journey, an insight into the mystical beauty of Sufism, and good manners. Hamadânî devoted most of his time to nurturing his disciples’ education and did not attempt to author books on a larger-scale. His works existed in the form of small-size treatise. Thus, the main purpose of this paper is to explain the Sufi terms used in Hamadânî’s works. Furthermore, it is anticipated that the findings of this study could be used as a reference for the researchers in this field.